Correlation between dental caries with quality of life in people and substance use disorder at the Lido Rehabilitation Center: a cross-sectional study - Parorrongan, Chrisanty Anastasia; Theresia, Tiarma Talenta; Louisa, Marie; Effendi, Nadira Zahrani; Putri, Anzany Tania Dwi; Putri, Resthie Rachmanta (Universitas Padjadjaran, 2025)
ABSTRACTIntroduction: Drug abuse is one of the concerning problems in Indonesia. It negatively impacts oral health, such as caries, xerostomia, periodontal disease, and tooth loss. Among these, dental caries is reported to be the leading cause of a reduction in quality of life. Although most oral health issues are not life-threatening, they significantly impact an individual's quality of life by extending periods of pain and discomfort. This study aims to analyze the correlation between dental caries and quality of life in individuals with substance use disorder (SUD) at the Lido Rehabilitation Center. Methods: This cross-sectional study was conducted at the Lido Rehabilitation Center, West Java, in August 2024. 101 SUD patients at the center were assessed through questionnaires and oral examinations. Dental caries served as the independent variable, while the quality of life (QoL), measured using the WHOQOL-BREF questionnaire across four domains (physical, psychological, social relationships, and environment), was the dependent variable. Data analysis using Spearman rank correlation to determine the correlation between QoL in the dental and non-dental caries groups and unpaired T-test to evaluate QoL scores in each domain for both dental and non-dental caries groups. Results: Significant differences were observed in the mean quality of life scores for the physical domain between the caries group (60,5 ± 13,78) and the non-caries group (65 ± 3,46), as well as for the social domain between the caries group (55,59 ± 19,29) and the non-caries group (58,33 ± 23,86). No significant correlation was found between quality of life scores and dental caries values. Conclusion: No correlation was found between dental caries and quality of life scores. Differences in QoL were observed between the dental and non-dental caries groups. Dental caries were higher among SUD patients compared to those without caries.KEYWORDS Quality of life, caries, drug abusers, drugs.